2014
DOI: 10.2119/molmed.2013.00117
|View full text |Cite
|
Sign up to set email alerts
|

α7 Nicotinic Acetylcholine Receptor Signaling Inhibits Inflammasome Activation by Preventing Mitochondrial DNA Release

Abstract: The mammalian immune system and the nervous system coevolved under the influence of cellular and environmental stress. Cellular stress is associated with changes in immunity and activation of the NACHT, LRR and PYD domains-containing protein 3 (NLRP3) inflammasome, a key component of innate immunity. Here we show that α7 nicotinic acetylcholine receptor (α7 nAchR)-signaling inhibits inflammasome activation and prevents release of mitochondrial DNA, an NLRP3 ligand. Cholinergic receptor agonists or vagus nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
138
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(146 citation statements)
references
References 30 publications
3
138
0
5
Order By: Relevance
“…A recent study also demonstrated that secreted phospholipase A2 IIA (sPLA2-IIA) mediated hydrolysis of the mitochondrial membrane contributed to mtDNA excretion which promoted leukocyte activation and inflammatory response [48]. Furthermore, acetylcholine significantly attenuated calcium or ROS stress induced mitochondrial damage and mtDNA release [49]. Together, mtDNA may be released extracellularly following cellular stress and damage in a manner dependent on cell and stimulus type, and elucidating the detailed molecular mechanism by which mtDNA release may provide underlying targets to treat various inflammatory diseases caused by mitochondrial malfunction [11, 44].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also demonstrated that secreted phospholipase A2 IIA (sPLA2-IIA) mediated hydrolysis of the mitochondrial membrane contributed to mtDNA excretion which promoted leukocyte activation and inflammatory response [48]. Furthermore, acetylcholine significantly attenuated calcium or ROS stress induced mitochondrial damage and mtDNA release [49]. Together, mtDNA may be released extracellularly following cellular stress and damage in a manner dependent on cell and stimulus type, and elucidating the detailed molecular mechanism by which mtDNA release may provide underlying targets to treat various inflammatory diseases caused by mitochondrial malfunction [11, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of a7 nAChR is essential to the integrity of the inflammatory reflex, because a7 nAChR knockout mice have an impaired inflammatory reflex. Vagus nerve stimulation fails to suppress inflammasome activity in these animals; and, moreover, activation of innate immunity in the a7 nAChR knockout mice produces significantly higher levels of TNF and the leaderless cytokines (Wang et al 2003;Lu et al 2014).…”
Section: Reflex Regulation Of Innate Immunitymentioning
confidence: 95%
“…Lymphocyte-derived acetylcholine is the neurally activated molecular mediator that binds to a7 nicotinic acetylcholine receptors expressed by red pulp and marginal zone macrophages (Wang et al 2003). Ligand receptor interaction inhibits the release of TNF through a molecular mechanism that has been attributed to formation of a heteroprotein complex comprised of a7 binding to JAK-STAT that suppresses activation of the nuclear translocation of nuclear factor kB and to stabilizing mitochrondrial membrane permeability (de Jonge et al 2005;Lu et al 2014). The functional importance of these T cells in this neural circuit is striking, because T-cell-deficient nude mice lack a working inflammatory reflex.…”
Section: Reflex Regulation Of Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Given that local paracrine and autocrine, as well as circadian, melatonin dampens astrocyte and mast cell reactivity, melatonin would also decrease BBBp and therefore the infiltration of invading leukocytes. It should be noted that melatonin is also a significant inducer of the alpha 7 nicotinic acetylcholine receptor (a7nAChr) [90], which, when activated, is a significant regulator of mitochondrial functioning and inflammasome activation [91], as well as being an inhibitor of glia and mast cell reactivity [92,93]. Mast cells are also a significant determinant of increases in human gut permeability to stress/ cortisol [6].…”
Section: Local Melatonin Synthesismentioning
confidence: 99%